2022
DOI: 10.3390/rs15010158
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BeiDou Observations on the Accuracy of Multi-GNSS PPP in a Function of Observing Session Duration within Europe—Analysis Based on Open-Source Software GAMP

Abstract: This study aims to verify whether the open-source software may provide Precise Point Positioning (PPP) with high accuracy. In this way, we address a question on the potential usability of open-source software for PPP analysis. On July 31, 2020, the full constellation of BeiDou satellites (SV) was announced. Over the European area, however, the number of visible BeiDou SVs is significantly smaller than in Asian-Pacific regions. Additionally, the system is in a modernization process, which may result in difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…In the paper [26], the authors concluded that the accuracy of PPP positioning could be improved by using BeiDou data. The time series of position components of selected EUREF Permanent Network (EPN) stations generated from sub-daily (30 min and longer) solutions was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In the paper [26], the authors concluded that the accuracy of PPP positioning could be improved by using BeiDou data. The time series of position components of selected EUREF Permanent Network (EPN) stations generated from sub-daily (30 min and longer) solutions was analyzed.…”
Section: Discussionmentioning
confidence: 99%